THE THEOLOGY OF RUWATAN TRADITION IN THE JAVANESE COMMUNITY IN KUMENDUNG VILLAGE MUNCAR DISTRICT BANYUWANGI - Relin D.E.; Ni Gusti Ayu Kartika; Jro Ayu Ningrat (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
The ruwatan tradition is one of the Javanese traditional ceremonies which is held after the farmers harvest the rice. This is meant to express gratitude because the rice plants have been successfully harvested and have produced a satisfying harvest. Besides that, the ritual is also a tribute to the ancestors who have passed away and pray that their sins will be forgiven by God. For the Javanese people, this annual activity called sadranan is an expression of social religious reflection so that it has implications for the realm of theology. Descriptively, this work describes aspects of the Hindu theology of this ruwatan tradition, that is, it leads to the form of devotion to God Almighty. Ruwatan is a form of expression of gratitude to God in its various manifestations. The purpose of the ruwatan ceremony is to remind that in humans there is evil and risks that humans may have to bear as a result, so that the worship of God becomes the focal point. Likewise, theologically, ruwatan is also said to be a traditional ceremony from an ancient tradition left over by animism (worship of ancestral spirits or ancestor spirits) that originated in ancient times and is a relic of an agrarian culture that is thousands of years old. The agrarian culture used to be very strong and the name of Java itself is often known as Jawa Dwipa which means rice island.